Primary aortoesophageal fistula: a rare cause of acute upper gastrointestinal bleeding - Samira Ineida Morais Gomes; Fernando Peixoto Ferraz de Campos; Brenda Margatho Ramos Martines; João Augusto dos Santos Martines; Edmar Tafner; Luis Masuo Maruta (University of São Paulo, 2011)
Acute upper gastrointestinal bleeding is a potentially life-threatening emergency, especially in the elderly. This condition accounts for approximately 1% of all emergency room admissions. Among the causes of such bleeding is aortoesophageal fistula, a dreaded but apparently rare condition, first recognized in 1818. The great majority of cases are of primary aortoesophageal fistula, caused by atheromatous aortic aneurysms or, less frequently, by penetrating aortic ulcer. The clinical presentation of aortoesophageal fistula is typically characterized by the so-called Chiari's triad, consisting of thoracic pain followed by herald bleeding, a variable, short symptom-free interval, and fatal exsanguinating hemorrhage. The prognosis is poor, the in-hospital mortality rate being 60%. Conservative treatment does not prolong survival, and the in-hospital mortality rate is 40% for patients submitted to conventional surgical treatment. Here, we report the case of a 93-year-old woman who presented to the emergency room with a history of hematemesis. The patient was first submitted to upper gastrointestinal endoscopy, the findings of which were suggestive of aortoesophageal fistula. The diagnosis was confirmed by multidetector computed tomography of the chest. Surgery was indicated. However, on the way to the operating room, the patient presented with massive bleeding and went into cardiac arrest, which resulted in her death.